Preliminary experience with high-density electroanatomical mapping for ablation of atrial fibrillation – Comparison of mini-basket and novel open irrigated magnetic ablation catheter in consecutive patients. (1st February 2017) - Kosiuk, Jedrzej; Hilbert, Sebastian; John, Silke; Bertagnolli, Livio; Hindricks, Gerhard; Bollmann, Andreas
Abstract: Background: Recently, a novel electroanatomic mapping system enabling rapid and automatic acquisition of high-resolution maps has been introduced. Previous reports focused on system use in combination with a mini-basket catheter. However, a novel system-specific, magnet-enabled ablation catheter eliminates the need for the mini-basket catheter and can potentially reduce procedure complexity and cost. Here we present our first experience from two consecutive case series using both procedural settings. Methods: In 14 consecutive patients (67 ± 9 years, 5 male) with paroxysmal (n = 10) or persistent AF (n = 4) undergoing de-novo (n = 8) or repeat (n = 6) AF ablation, left atrial electroanatomical maps were acquired with a mini-basket and in 22 patients (64 ± 9 years, 17 male) with paroxysmal (n = 4) or persistent AF (n = 18) undergoing de-novo (n = 12) or repeat (n = 10) AF ablation with the new ablation catheter. Results: Both complete (7.9 [IQR 4.5–16.2] vs 18.8 [IQR 12.0–25.5] minutes, p = 0.005) and partial maps (3.0 [IQR 2.0–4.6] vs 4.5 [IQR 2.0–6.0] minutes, p = 0.014) acquired with mini-basket required significantly shorter mapping time and had higher point density: 8832 ± 4809 vs 4460 ± 3914 (p = 0.014) and 2483 ± 1774 vs 1111 ± 1926 data points (p = 0.002) in partial maps. However, procedural (201 ± 52 vs 159 ± 29 min, p = 0.004) and fluoroscopy time (33 ± 11 vs 25 ± 6 min, p = 0.005) was significantly higher in the mini-basket group. Procedural endpoints and complications rates were similar in both groups. Conclusion: The high-density mapping system can successfully be used with both mini-basket catheters and ablation catheters employed for electro-anatomic reconstruction of the left atrium. While mapping is faster and point density higher with the mini-basket, procedure and fluoroscopy times are longer. The clinical significance of those findings needs to be investigated in future and larger studies.